Persistence of viable opportunistic pathogens in a multi-stage natural wastewater treatment system - Hazem Aqel; Husni Farah; Ramy Fodah; Naif Sannan; Ola Surakhi (PLoS ONE, 2026)
Nature-based wastewater treatment systems are increasingly implemented to support water reuse in arid regions, yet their effectiveness in removing viable culturable opportunistic pathogens remains insufficiently characterized. In this exploratory, culture-based study, we assessed bacterial population dynamics across a five-stage natural wastewater treatment system (Wadi Hanifa, Riyadh, Saudi Arabia), tracking culturable bacteria from secondary-treated influent to sand-filtered effluent. Water samples were collected at five sequential treatment stages and analyzed for physicochemical parameters, total culturable bacterial abundance, bacterial diversity, taxonomic composition, and antimicrobial susceptibility of persistent isolates. Total culturable bacterial counts decreased by approximately 1.1 log 10 CFU mL ‒1 across the system, accompanied by an approximately 50% reduction in observed isolate richness. The fecal indicator Escherichia coli was detected only in upstream and intermediate stages (sampling locations L3.1-L3.3) and was absent from downstream samples. In contrast, the opportunistic pathogen Klebsiella pneumoniae was recovered across all five treatment stages and accounted for 44.4% (8/18) of all morphologically distinct isolates grown on the selected culture media. Turbidity declined by 71% along the treatment train and showed a strong positive correlation with bacterial richness (Kendall’s τ = 0.84, p = 0.038), although this exploratory correlation should be interpreted with caution given the small sample size (n = 5 stages). Phenotypic antimicrobial susceptibility testing revealed multidrug resistance (MDR) in 62.5% (5/8) of K. pneumoniae isolates, although all remained susceptible to amikacin and meropenem. Under the conditions examined, multi-stage natural wastewater treatment substantially reduced overall bacterial abundance and diversity but did not eliminate viable, multidrug-resistant Klebsiella pneumoniae . The discordance between fecal-indicator removal and opportunistic pathogen recovery highlights system-specific limitations of indicator-based monitoring for assessing microbial safety in wastewater reuse systems. Given the limited isolate number (n = 8 K. pneumoniae ) and the absence of molecular resistance-gene characterization, broader claims about wastewater as a dissemination pathway for antimicrobial resistance cannot be drawn from these data. These findings are based on a single cross-sectional sampling event and should be considered hypothesis-generating rather than confirmatory.